Pengembangan Media Pembelajaran Fisika Berbasis Game Edukasi: Analisis Bibliometrik Menggunakan Software VOSViewer (2017-2022) - Rahmawati, Yulika; Febriyana, Monica Merry; Bhakti, Yoga Budi; Astuti, Irnin Agustina Dwi; Suendarti, Mamik (Universitas PGRI Semarang, 2022)
Physics is one of the abstract subjects that require visualization so that learning media is needed so that students are able to understand the concepts studied. One of the learning media that displays visualization by utilizing technology in the form of educational games. This study aims to analyze the development of educational game learning media in physics learning with a bibliometric approach using VOSViewer software. The method used in this study is bibliometric analysis. There are 6 clusters of classification through VOSViewer software. The results of the study obtained articles used with the title